Workplace Behaviour and Personnel Job Performance in Ministries of Education in North- Central States, Nigeria - Ayinde, Yusuf; OYEDEJI, N. B.; OMOSIDI, A. S. (International Journal of Educational Management, 2021)
This research investigated the relationship between workplace behaviour and personnel job performance achievement in Ministries of Education in North-central States, Nigeria. Specifically, the research assessed: (i) the relationship between punctuality and personnel job performance; (ii) the relationship between teamwork and personnel job performance and (iii) the relationship between discipline and personnel job performance. The study was a descriptive research design of correlation type, random sampling technique was used to select three states (Kwara, Nasarawa and Niger) out of the six states in the Geo-political Zone while random sampling technique was used to select all the three State Ministries of Education in these states. Random sampling technique was used to select 503 staff out of the 878 in the selected states ministries of education, and 145 principal officers (Directors,Assistant and Deputy Directors) out of the 235 in the selected states which constitutes 60%.. Questionnaire was used to collect data for the study, the instruments were validated by the experts and also tested for reliability. The reliability coefficients realised for WPQ and PJPQ were 0.75 and 0.86 respectively. Main and operational hypotheses were tested using Pearson product-moment correlation statistics respectively at 0.05 level of significance. The findings revealed that there was a significant relationship between workplace behaviour and personnel job performance (p<0.05). The study concluded that workplace behavior plays significant role in enhancing personnel job performance which would consequently facilitate realisation of institutional goals in Ministry of Education in North- central States, Nigeria. Based on the findings and conclusion, it is therefore recommended that, state government needs to intensify efforts to ensure that staff maintain workplace behavior through strict implementation of staff code of conduct and ensure that appropriate sanctions are carried out on the defaulters.